SULTAN HASANUDDIN'S COMIC BOOK AS A MEDIA FOR DELIVERING INDONESIAN HISTORY - Kurniawan, Sulistyo Agung Dwi; Syafii, Syafii; Budi Utomo, Kamsidjo (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
This study project was motivated by the decreasing interest in reading among adolescents, especially reading books on history, the decreasing reading rate resulting in less information absorption so that they forgot the importance of studying history. Because of this problem, the writer has the idea to bring back the big story that has happened in Indonesian history with a more modern look with the title